Mapping Titan's HCN in the far infra-red: implications for photochemistry. - Teanby, N; Irwin, P; de Kok, R; Nixon, C (2010)
Observations of Titan's far infra-red spectra by the Cassini orbiter's Composite InfraRed Spectrometer have been used to determine the latitude distribution of HCN at 1 mbar by fitting the HCN and CO rotational lines in the 18-60 cm(-1) (160-550 microm) spectral range. Results confirm the north polar HCN enrichment previously observed using mid-IR data and support the conclusion that Titan's nitrile species are significantly more enriched than hydrocarbons species with similar predicted photochemical lifetimes. This suggests Titan's photochemical cycle includes an additional sink for nitrogen bearing species. The abundance of CO was also determined, and had a mean value of 55 +/- 6 ppm at 20 mbar. However, it was not possible to reliably determine the CO latitude variation due to unconstrained temperatures in the north polar lower stratosphere.